FROM “FAILURE OF POLITICS” TO THE IMPERATIVE OF SURVIVAL: THE CONCEPTUAL TRANSFORMATION OF SECURITIZATION THEORY IN THE CONTEMPORARY ERA - Bozhko, Yaroslav (Public Management and Policy, 2026)
Under the conditions of modern international anarchy, a state’s capacity for rapid mobilization takes precedence over adherence to the procedures of “normal politics.” This research proposes a departure from the normative stigmatization of security measures and substantiates the “security state” model, wherein the priority of efficiency and sovereignty protection dissolves the traditional dichotomy between security and liberty. The relevance of this study is driven by the need to reconceptualize the phenomenon of securitization, which, under the pressure of an anarchic environment, is evolving from a temporary instrument into a permanent principle of political space organization. The article aims to analyze the transformation of securitization theory in contemporary discourse and to justify the shift in the status of security practices from “normative aberrations” (“a failure of politics”) to decisions essential for state survival (the “security state”) amidst technological change. The study is based on the methodology of qualitative conceptual analysis and critical synthesis. An interpretivist approach is applied to compare the liberal-institutional view, structural and neoclassical realism, the theory of “Just Securitization”, and the sociological approach of the Paris School. The article proves the theoretical inadequacy of the liberal approach, which viewed securitization as a “pathology,” in the context of the “relative gains” dilemma. Based on neoclassical realism, it is shown that for democracies prone to “underbalancing” and strategic inertia, securitization serves as a necessary tool for resource mobilization. The role of ontological security is analyzed, explaining states’ need for stable identity narratives to preserve their agency. Special attention is paid to the “technological turn”: it is substantiated that the development of mass surveillance and the automation of warfare transform securitization into a “pragmatic act” that precedes political decisions. It is revealed that in the modern world, democracy is forced to adapt to the logic of efficiency to withstand authoritarian threats. It is concluded that the “security vs. Democracy” dichotomy is losing its relevance. The formation of a “security state” model, where the state of emergency becomes permanent, is an inevitable reaction to structural anarchy and technological challenges. Securitization today is not an elite choice but an unavoidable mechanism for preserving sovereignty and ensuring the physical survival of the political nation.